Ekstrak Etanol Buah Jeluak (Microcos Tomentosa) sebagai Antioksidan dengan Metode DPPH - Mastura, Mastura; Wati, Julina; Mauliza, Mauliza (Universitas Samudra, 2022)
Indonesia is known as one of the largest medicinal plant user countries in the world. There are several plants that have potential as medicine, such as the Jeluak (Microcos tomentosa) plant. The purpose of this study was to determine the antioxidant activity of the ethanolic extract of Jeluak Fruit (Microcos tomentosa). The ethanol extract was obtained through the maceration method. Antioxidant testing was carried out by free radical scavenging method with 2,2-diphenyl-1-picrylhydrazyl (DPPH). The results of the study based on phytochemical screening tests showed that the ethanolic extract of jeluak fruit (Microcos tomentosa) contains secondary metabolites of alkaloids, saponins, flavonoids, and terpenoids. The results of the study based on antioxidant testing showed that the highest percentage of inhibition of Jeluak Fruit (Microcos tomentosa) at a concentration of 100 ppm was 92.22%. The IC50 value of the ethanolic extract of Jeluak Fruit (Microcos tomentosa) showed a very strong antioxidant activity of 4.34 ppm. Based on this research, it can be concluded that the ethanolic extract of Jeluak Fruit (Microcos tomentosa) has potential as an antioxidant.